Molecular recognition of aliphatic amines by luminescent Zn-porphyrins - Oriol Penon; Artur J. Moro; Davide Santucci; David B. Amabilino; Lima, Joao Carlos; Perez-Garcia, Lluisa; Rodriguez, Laura (Inorganica Chimica Acta, 2014)
n/a
Lima, Joao Carlos/K-2890-2014; Penon, Oriol/C-9707-2014; Perez-Garcia, Lluisa/H-4384-2013; Amabilino, David/D-4671-2012; Lima, Joao/F-3658-2010; Rodriguez, Laura/A-4169-2011; Moro, Artur/C-6689-2013 Penon, Oriol/0000-0003-0811-9631; Perez-Garcia, Lluisa/0000-0003-2031-4405; Amabilino, David/0000-0003-1674-8462; Lima, Joao/0000-0003-0528-1967; Rodriguez, Laura/0000-0003-1289-1587; Moro, Artur/0000-0003-3285-4919 0